2018
DOI: 10.1002/wics.1435
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating MCMC algorithms

Abstract: Markov chain Monte Carlo algorithms are used to simulate from complex statistical distributions by way of a local exploration of these distributions. This local feature avoids heavy requests on understanding the nature of the target, but it also potentially induces a lengthy exploration of this target, with a requirement on the number of simulations that grows with the dimension of the problem and with the complexity of the data behind it. Several techniques are available toward accelerating the convergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 98 publications
0
72
0
Order By: Relevance
“…Separate pooled meta-analyses of survival benefits associated with GTR of glioblastoma were determined for publications contributed by members of genealogy A (neurosurgeons) and B (radiation oncologists), as well as non-genealogy members. To determine whether the observed disparity was random, we performed χ 2 -based Monte Carlo simulations with a pvalue based on 10,000 simulations [30]. Monte Carlo simulations were executed by randomly selecting 6 and 20 studies from all articles identified in our literature search (matching the number of articles contributed by the radiation oncology genealogy and neurosurgery genealogy, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Separate pooled meta-analyses of survival benefits associated with GTR of glioblastoma were determined for publications contributed by members of genealogy A (neurosurgeons) and B (radiation oncologists), as well as non-genealogy members. To determine whether the observed disparity was random, we performed χ 2 -based Monte Carlo simulations with a pvalue based on 10,000 simulations [30]. Monte Carlo simulations were executed by randomly selecting 6 and 20 studies from all articles identified in our literature search (matching the number of articles contributed by the radiation oncology genealogy and neurosurgery genealogy, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the number of training parameters does not increase with the dimensionality of the problem but only depends on the number of categories (i.e., labels) and features used in the model. The main challenge in extending the current model to 3-D will be the increase in computational time for both training and simulation steps, which could be addressed by implementing more advanced optimization and sampling methods such as incremental gradient decent (Mokhtari et al, 2018) and parallel multiple proposal MCMC algorithms (Calderhead, 2014;Robert et al, 2018).…”
Section: Water Resources Researchmentioning
confidence: 99%
“…This algorithm was shown to be capable for Bayesian inversion of multi‐Gaussian subsurface properties in many applications (e.g., Cotter et al., 2013; Hu et al., 2017; Iglesias et al., 2012). Still, when pCN‐MCMC explores the target posterior distribution, it may still need a long chain and it is still difficult to explore a large potential model space since the MCMC simulation proceeds by local jumps in the vicinity of the current solutions (Robert et al., 2018). Parallel tempering can handle the dilemma with exploring large model spaces and can improve the efficiency of exploring the target posterior by exchange swaps between cold chains and hot chains.…”
Section: Introductionmentioning
confidence: 99%